(untitled) (Jurnal Mekanikal, 2019)
Combustion and burning velocity of hydrogen enriched biogas-air mixture have been investigated in this study from an equivalence ratio of 0.4 up to stoichiometric. Hydrogen addition was varied from 10 to 40% based on the volume fraction. Flame buoyancy was observed for leaner mixture especially at an equivalence ratio of 0.4, while mild cellularity was observed for the equivalence ratios of 0.4 and 0.5 during the later stage of the flame propagation. Flame appears to become less stable under leaner conditions as supported by the occurrence of buoyancy and mild cellularity at the equivalence ratios of 0.4 and 0.5 under 30% and 40% of hydrogen addition. It was found that for 30% and 40% addition, the flammability limits extend to the leaner side. The maximum burning velocity occurs at an equivalence ratio of 0.8 for all mixtures regardless of the hydrogen enrichment percentage. The flame speed was enhanced with hydrogen enrichment at higher than 30% which led to a significant increase in the burning velocity These observations show that the addition of hydrogen into biogas combustion will lead to an increase in the flame propagation and burning velocity.